2019
DOI: 10.3390/risks7040106
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Timing in CPF Investment Funds in Singapore: Do They Outperform Non-CPF Funds?

Abstract: The purpose of this study is to examine the volatility-timing performance of Singapore-based funds under the Central Provident Fund (CPF) Investment Scheme and non-CPF linked funds by taking into account the currency risk effect on internationally managed funds. In particular, we empirically assess whether the funds under the CPF Investment Scheme outperform non-CPF funds by examining the volatility-timing performance associated with these funds. The volatility-timing ability of CPF funds will provide the CPF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… Moreira and Muir (2019) suggested that funds managers who do not time volatility face a significant risk of losing funds’ value. To test for volatility timing, we use the Busse (1999) framework as employed previously by Shen et al (2019) . We specify the functional form of volatility timing as below: …”
Section: Data and Research Methodologymentioning
confidence: 99%
“… Moreira and Muir (2019) suggested that funds managers who do not time volatility face a significant risk of losing funds’ value. To test for volatility timing, we use the Busse (1999) framework as employed previously by Shen et al (2019) . We specify the functional form of volatility timing as below: …”
Section: Data and Research Methodologymentioning
confidence: 99%
“…As COVID-19 outbreak is marked with high volatility, a holistic view on funds’ performance is not complete without assessing their response to varying volatility. For this, we employ Busse ( 1999 ) basic methodology as used by Shen et al ( 2019 ) recently. The functional form is as follows …”
Section: Empirical Strategymentioning
confidence: 99%
“…Moreira and Muir (2019) suggested that funds managers who do not time volatility face a significant risk of losing funds' value. To test for volatility timing, we use the Busse (1999) framework as employed previously by Shen et al (2019). We specify the functional form of volatility timing as below:…”
Section: Volatility Timing During Pandemicmentioning
confidence: 99%